Cognitive linguistics : current applications and future perspectives - Kristiansen, Gitte, 1966- (Applications of cognitive linguistics, 2006)
Cognitive Linguistics: Current Applications and Future Perspectives is an up-to-date survey of recent research in Cognitive Linguistics and its applications by prominent researchers. The volume brings together generally accessible syntheses and special st.